ARF6, induced by mutant Kras, promotes proliferation and Warburg effect in pancreatic cancer. (1st March 2017) - Liang, Chen; Qin, Yi; Zhang, Bo; Ji, Shunrong; Shi, Si; Xu, Wenyan; Liu, Jiang; Xiang, Jinfeng; Liang, Dingkong; Hu, Qiangsheng; Ni, Quanxing; Yu, Xianjun; et al.
Abstract: Though significant progress has been made in the availability of diagnostic techniques and treatment strategies, pancreatic cancer remains a disease of high mortality rates. Therefore, there is an urgent need for a better understanding of the molecular mechanisms that governs the oncogenesis and metastasis process of pancreatic cancer. In our study, by using the Cancer Genome Atlas (TCGA) dataset analysis, we demonstrated that the small guanosine triphosphatase (GTPase) ADP-ribosylation factor 6 (ARF6) serves as a biomarker for predicting prognosis of pancreatic cancer. In vitro studies demonstrated that silencing ARF6 expression reduced cell proliferation and attenuated the Warburg effect. Moreover, we observed that ARF6 was a downstream target of Kras/ERK signaling pathway, and the strong correlation of expression between Kras and ARF6 in the TCGA dataset further confirmed this observation. Taken together, our novel findings suggest ARF6, a target of mutant Kras, may promote pancreatic cancer development by enhancing the Warburg effect. Highlights: ARF6 predicts poor prognosis and plays oncogenic roles in pancreatic cancer cells. ARF6 is responsible for maintaining the Kras-induced activation of ERK1/2. ARF6 leads to enhancement of c-Myc expression and concomitant aerobic glycolysis. ARF6 cooperates with Kras/ERK axis to sustain growth of pancreatic cancer cells. ARF6 is a downstream target of c-Myc and forms a positive loop with c-Myc.